Two-tissue stable isotope analysis to elucidate isotopic incorporation and trophic niche patterns for chubbyhead barb Enteromius anoplus - Kambikambi, Manda Juliet (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2018)
Knowledge of trophic ecology underpins conservation and management of threatened species. Stable isotope analysis has been widely used as a more objective approach for elucidating the trophic positions of freshwater fishes. Until recently, stable isotope analysis for trophic ecology studies in freshwater fishes largely utilised white muscle tissue. This sampling approach, however, involves either euthanasia or muscle biopsy procedures that may be inappropriate for small-sized and endangered fishes. These concerns raised the need to explore and validate the utility of non-lethal alternatives such as fin clips, mucus and scales. The present study investigated the use of caudal fin tissue as a potential non-lethal alternative to muscle tissue for trophic studies on the chubbyhead barb Enteromius anoplus. The chubbyhead barb was selected as a model taxon for the present study because it is closely related or comparable in body size to a number of highly threatened small-bodied minnows in southern Africa. The chubbyhead barb was also considered an ideal species for this study because it is widespread, abundant and classified as Least Concern on the IUCN list of threatened species. The study used a two-pronged approach based on laboratory and field experiments. A laboratory experiment was conducted to quantify isotopic turnover rates and diet-tissue discrimination factors (DTDFs/A) for both muscle and fin tissues. This involved feeding chubbyhead barb two diets with distinct carbon (Î´13C) and nitrogen (Î´15N) values, and monitoring the temporal isotopic incorporation patterns into the two tissues. These patterns were assessed by applying least squares non-linear one- and two-compartment isotopic kinetics models. Model comparisons, based on Akaike information criterion (AIC), revealed that one- compartment models described isotopic incorporation patterns better than two-compartment models for both muscle and fin tissues. For Î´13C, relatively short and comparable turnover rates were observed for muscle and fin tissues, which suggests that fin tissue could potentially provide similar inference as muscle tissue when assessing short term dietary patterns for chubbyhead barb. In contrast to Î´13C, turnover rates for Î´15N between muscle and fin tissue were different for both diets. Specifically, stable isotope incorporation turnover rate was faster in muscle tissue for animals that were fed on isotopically enriched diets compared to fin tissue. Conversely, stable isotope incorporation into fin tissue was faster in animals fed on isotopically depleted diets compared to muscle tissue. This suggests that knowledge of animal diet is critical when inferring fin tissue Î´15N turnover rates, particularly when extrapolating both short and long term dietary patterns. Diet-tissue discrimination factors were influenced by diet type, with the fish fed on isotopically enriched diet having lower DTDFs than animals fed on isotopically depleted diets. This variation may be explained by the protein quality hypothesis, which suggests that the DTDFs of consumers will decrease as protein quality increases. When A13C and A15N values were averaged across diets in muscle and fin tissue, the values were 0.74"° and 0.64"°, respectively, for A13C, and 5.53"° and 5.83 "°, respectively, for A15N. This appeared to be consistent with studies on other taxa for A13C (0-1 "°), but for A15N (3-5 "°) the results of this study were higher than those reported for other taxa. These results suggest that investigating appropriate DTDFs for both muscle and fin tissues is important in trophic ecology studies of these minnows. A field-based study was conducted to investigate temporal dynamics in food web patterns for chubbyhead barb in the wild within the headwaters of the Koonap River, a tributary of the Great Fish River, in the Eastern Cape, South Africa. This was achieved by collecting and comparing stable isotope data for chubbyhead barb and its potential food sources on a seasonal scale. There was a discernible difference in both the composition of carbon and nitrogen isotope values for basal food sources and macroinvertebrate communities, which suggests that this headwater stream was subject to temporal changes in food web dynamics. For chubbyhead barb, comparison of its isotopic niche sizes on a temporal scale based on both muscle and fin tissue showed differences across seasons. Furthermore, isotopic niche sizes inferred from fin tissue were larger than those inferred from muscle tissue during winter and spring, whereas during summer and autumn the isotopic niche sizes inferred from muscle and fin tissue were generally comparable. This suggests the likely influence of different metabolic and physiological processes that these two tissues undergo on a temporal scale. Therefore, difference in tissue type, and their associated metabolic pathways should be considered when using fin tissue as a substitute for muscle tissue on broad temporal scales. The results from this study indicated that caudal fin tissue has the potential to be a substitute for muscle in trophic studies of chubbyhead barb Enteromius anoplus, as well as other related small bodied endangered minnow species from South Africa.
Keywords: Food chains (Ecology); Barbus -- South Africa -- Great Fish River Estuary; Stable isotopes; Freshwater fishes -- Feeding and feeds; Freshwater fishes -- Food; Fins (Anatomy); Akaike Information Criterion; Freshwater fishes -- Conservation; Chubbyhead barb Enteromius anoplus